Sustainable development of the Republic of Bashkortostan of the Russian Federation: current state and prospects - Yu. K. Akchulpanov (Вестник университета)
The issues and prospects of sustainable development of the Republic of Bashkortostan with a focus on innovation aspects have been considered in order to develop recommendations to ensure the long-term progress of the region. The research methodology is based on the analysis and comparison of economic, social, and environmental factors of sustainable development, assessment of the role of innovation in each sphere, study of successes and experience of other constituent entities of the Russian Federation and foreign countries, as well as on the proposals for creating regional centers for assessing and monitoring sustainable development that in their activities will be focused on comprehensive research in regional socio-economic systems, considering the innovation component. The main spheres and components of ensuring sustainable development of the region have been defined and presented. The main study results are: identification of key aspects of sustainable development of the Republic of Bashkortostan; identification of issues and prospects in developing the economy and social and environmental spheres; analysis of the role of innovation in ensuring sustainable development; recommendations development for creating regional centers for assessing and monitoring sustainable development. Sustainable development of the territory is one of the main strategic objectives of the constituent entity. In order to achieve it, it is necessary to continue the work, as well as to increase attention to innovations, education and management systems. The centers creation can contribute to the system analysis and assessment of sustainable development processes, as well as the development of recommendations and strategies to improve the economic, social, and environmental condition of the territory.